The Influence of Remembrance on Sobriety Modern Society at Café Rumi - Zaranggi, Ahmed (Proceeding International Conference on Science and Engineering, 2019)
The spiritual crisis is so much engulfed by the urban community with its materialistic life, this leads to a vacuum of heart and leads to serious stress and turmoil. This turmoil mobilized everyone to overcome it, including Café Rumi worshipers. A spiritual café that offers spiritual needs that are being sought by the urban community. Through the application of routine zikir rituals, it can be a solution to this problem This study aims to find out whether the typical ritual remembrance activities at Café Rumi can have a significant impact and influence on the sobriety of the pilgrims who regularly attend zikir activities that are there. This study uses qualitative methods with descriptive analysis approach through direct observation, in-depth interviews and documentation process. After that, it is done with the data analysis process, compared, described later until the final conclusions are obtained. The target of being a researcher is the Cafe Rumi congregation, most of whom are city residents. This study yields conclusions in the form of the meaning of remembrance in Café Rumi is not merely a ritual but rather a zikir in an act of sharing with others. And from the reading side there is a modification of the addition and subtraction of the number of zikir. Zikir activities are carried out in three forms, namely spiritual meditation with zikir together led by kiyai, culture through sholawatan and Sufi dances accompanied by hadrah music, and social activities in the form of sharing food to people in need at a crossroads. The ritual of the typical Sufi ritual of remembrance is also able to increase the sobriety for worshipers at Café Rumi.